1998
DOI: 10.1203/00006450-199806000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Different Meaning of CD38 Molecule Expression on CD4+ and CD8+ Cells of Children Perinatally Infected with Human Immunodeficiency Virus Type 1 Infection Surviving Longer than Five Years

Abstract: We investigated the relationship between CD4+CD38+, CD4+HLA-DR+, CD8+CD38+, and CD8+HLA-DR+ cell proportions (HLA-DR = major histocompatibility complex class II) (determined by two-color immunofluorescence) and the clinical condition, IL-2 and IL-6 production, viral RNA copy numbers, and the eventual immunologic-virologic course in 25 children perinatally infected with HIV-1 surviving longer than 5 y [median age, 92 (range, 63-136) mo]. Twelve healthy age-matched children were studied as control subjects. HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 42 publications
8
49
0
Order By: Relevance
“…The %CD8 ϩ CD38 ϩ and CD8 ϩ (CD38 ϩ ) measurements are highly correlated, but the latter is preferable because of the heterogeneous expression of CD38 on the cell surface (2,6,12,13). This study confirmed that CD38 expression on CD8 ϩ T cells is negatively correlated with age (2, 8, 11) and increased in HIV-infected children in comparison to HIV-uninfected age-matched controls (1,4,5,8,9). These findings are consistent with CD38 being a marker of immaturity and immune activation.…”
Section: Discussionsupporting
confidence: 71%
“…The %CD8 ϩ CD38 ϩ and CD8 ϩ (CD38 ϩ ) measurements are highly correlated, but the latter is preferable because of the heterogeneous expression of CD38 on the cell surface (2,6,12,13). This study confirmed that CD38 expression on CD8 ϩ T cells is negatively correlated with age (2, 8, 11) and increased in HIV-infected children in comparison to HIV-uninfected age-matched controls (1,4,5,8,9). These findings are consistent with CD38 being a marker of immaturity and immune activation.…”
Section: Discussionsupporting
confidence: 71%
“…As opposed to what occurs in adults, these results suggest that CD38 is a marker of cell immaturity rather than cell activation in CD4 + T cells in children [37,38]. Finding that its expression is high in naive CD4 + T cells [39], that it decreases over time [40] and that it increases in CD4 + T cells during immune reconstitution [37,38] all support this concept. Besides representing a marker of cell immaturity, CD38 in CD4 + T cells is likely to have multiple functional activities [37].…”
Section: Cd38mentioning
confidence: 77%
“…Liver disease was defined as previously reported (12 Interleukin-6 in vitro release. As previously described (3,4), PBMC were separated from EDTAtreated blood by centrifugation over Ficoll-Hypaque (␦ 1.077 g/cm 3 ; Pharmacia Biotech, Uppsala, Sweden) and resuspended at 10 6 cells/mL in RPMI 1640 (GIBCO Laboratories, Grand Island, NY) containing 0.5% penicillin, 0.5% streptomycin, 1% glutamine. Viable cell numbers were determined by trypan blue exclusion.…”
Section: Methodsmentioning
confidence: 99%